Argininemia as a cause of severe chronic stunting in a low-resource developing country setting: a case report. Issue 1 (December 2016) - King, Nora; Alvizures, Romina; García, Pablo; Wessel, Ann; Rohloff, Peter
Abstract Background Argininemia is rare inborn error of metabolism which, when untreated, presents in late infancy with growth delay and developmental regression. In developed countries, argininemia is diagnosed early by newborn screening and is treated immediately with a protein-restricted diet. In developing countries, diagnosis may be delayed by the assumption that stunting is related to malnutrition alone. Case presentation We describe the diagnosis and treatment of argininemia in a 60-month-old Kaqchikel Maya girl in rural Guatemala. The patient initially presented with severe stunting and developmental regression. The initial diagnosis of argininemia was made by a screening test in dried blood spots and confirmed with urine and serum amino acid profiles. The patient was treated with a low-protein diet using locally available foods, leading to significant improvement in her growth and development. Conclusions This case demonstrates that the identification, diagnosis and treatment of IEM in developing countries are increasingly feasible, as well as ethically imperative. Providers working with malnourished children in developing countries should suspect IEM in malnourished children who do not respond to standard therapies.